Impact of Dose Reduction of Afatinib Used in Patients With Non–Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Wang, Ziyu; Du, Xin; Chen, Ken; Li, Shanshan; Yu, Zhiheng; Wu, Ziyang; Yang, Li; Chen, Dingding; Liu, Wei (Frontiers in Pharmacology, 2021)
Background and Aim: As one of the second-generation epidermal growth factor receptor (EGFR)–tyrosine kinase inhibitors, afatinib brings survival benefits to patients with common and rare EGFR mutations. This study aimed to compare the effectiveness and safety of 30 mg and 40 mg of afatinib in patients with non-small-cell lung cancer (NSCLC) using qualitative and quantitative analysis methods so as to provide guidance for clinical medication. Methods: The PubMed, Embase, ClinicalTrials.gov, the Cochrane Library, China National Knowledge Infrastructure, and WanFang databases were thoroughly searched from inception to February 26, 2021. Two researchers independently screened the literature, extracted data, and evaluated the quality. Revman and Stata 15.0 were used for meta-analysis. Results: Twelve cohort studies including 1290 patients for final analysis were selected; of which, 1129 patients were analyzed to measure the effectiveness outcomes and 470 patients for safety outcomes. In patients with non-brain metastasis, the progression-free survival of the first- or second-line treatment with reduced-dose afatinib was equivalent to the conventional dose. In terms of safety, the reduced dose could significantly lower the incidence of severe diarrhea and severe rash, but not the total incidence of diarrhea, rash, and all levels of paronychia. Conclusions: The incidence of common serious adverse reactions was significantly lower with 30 mg of afatinib compared with 40 mg of afatinib in patients with NSCLC. The effectiveness appeared to be similar to that in patients with non-brain metastasis. This study provides a reference for clinical dose reduction of afatinib.